Primary Issues in the Selection of Surgical Procedures for Thoracic and Lumbar Spinal Tuberculosis - Shi, Jian‐dang (Orthop Surg, 2014)
Debridement, spinal canal decompression, deformity correction, bone graft fusion and internal fixation are commonly used in the surgical treatment of spinal tuberculosis. A complete surgical plan for patients with spinal tuberculosis may include all or some of these five surgical procedures that involve both removing tuberculous lesions and re‐establishing spinal stability and function. All five procedures can be carried out via an anterior or posterior approach or a combination of these two approaches. A combined posterior–anterior approach is becoming a preferred choice for treating spinal tuberculosis. However, this procedure requires two incisions and two rounds of surgeries, which the associated extensive surgical trauma. Thus, a simple anterior or posterior approach may be preferable. Each of these approaches has its own advantages and disadvantages that must be considered during the clinician's evaluation. Selection of the most appropriate of these three approaches is vital to achieving cure of spinal tuberculosis. Spinal surgeons should comprehensively consider each patient's characteristics, the manifestations of their lesions and how familiar the surgeon is with the required surgical procedure(s). The primary consideration should be the potential outcome: the effectiveness of debridement is the key determinant of the surgical outcome.